2019
DOI: 10.26550/2209-1092.1039
|View full text |Cite
|
Sign up to set email alerts
|

The impact of improved surgical safety checklist participation on OR efficiencies: A pretest-posttest analysis

Abstract: BMG conceived of the study, assisted in participant recruitment and drafted the manuscript. BMG and EH performed the quantitative analysis. AM and EH contributed to study conception and assisted in interpretation. TG, JL and TKW assisted in recruitment, participated in the study and assisted in interpretation. All authors participated in the design and coordination of the study and read and approved the final manuscript. The impact of improved surgical safety checklist participation on OR efficiencies: A prete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…A common misconception that impacted attitudes and fostered resistance was the belief that the surgical safety checklist reduced operating theatre efficiency. While this barrier has been disproved in several studies demonstrating that the application of the checklist does not cause or compound surgical delays, this review has underscored that this view remains a wide-held misconception (Gillespie et al, 2019;Papaspyros et al, 2010). Therefore, affording the opportunity for evidence-informed education and training sessions, as well as implementing local champions, may help to combat these inaccurate staff perceptions to better facilitate and promote effective implementation of this checklist.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A common misconception that impacted attitudes and fostered resistance was the belief that the surgical safety checklist reduced operating theatre efficiency. While this barrier has been disproved in several studies demonstrating that the application of the checklist does not cause or compound surgical delays, this review has underscored that this view remains a wide-held misconception (Gillespie et al, 2019;Papaspyros et al, 2010). Therefore, affording the opportunity for evidence-informed education and training sessions, as well as implementing local champions, may help to combat these inaccurate staff perceptions to better facilitate and promote effective implementation of this checklist.…”
Section: Discussionmentioning
confidence: 90%
“…Time constraints compounded with increasing workloads impacted the ability of staff to participate in the checklist because of simultaneous competing perioperative clinical tasks and tending to patient care. It has been identified that checklist completion was especially disruptive during ‘time out’ and ‘sign out’ as these are arguably the busiest points of the surgical procedure (Fourcade et al, 2012; Gillespie et al, 2019). During these times, the anaesthetic team is focused on managing the patient's airway and the scrub team is simultaneously setting up equipment, impeding their ability to participate.…”
Section: Discussionmentioning
confidence: 99%
“…Esse dado diverge do encontrado em estudo norteamericano com análise de 7.265 cirurgias ortopédicas, no qual não observou diferença significativa no tempo de permanência do paciente na sala de cirurgia e no tempo de operação 17 . Resultado diverso também foi relatado em investigação australiana acerca dos impactos da introdução de checklist, e que não identificou diferenças no tempo de permanência do paciente na sala cirúrgica até o início do procedimento ortopédico, tampouco no tempo relacionado ao término da cirurgia e a saída do paciente da sala 18 .…”
Section: Discussionunclassified
“…The incomplete filling of the instrument is a phenomenon that can occur in other scenarios 1,15,17,20 . Different studies reported that the challenge of the checklist implementation continues, both in Brazil and worldwide, and suggestions aimed at better enforcement of the process involve professionals from all specialties 28 . As for the filling, it requires engagement of the operating room staff for greater adhesion 16 .…”
Section: Presence Of the Checklist In The Medical Records And Data Co...mentioning
confidence: 99%
“…The challenge remains of greater adherence to the checklist use by professionals at all stages, as well as of the promotion of continuing education in health services 27 . The use of the instrument requires a dynamic and co-participative intervention 28 , since in the opinion of nurses and surgeons, disagreements and conflicts still occur 27,30 . We emphasize that new technologies have been implemented, seeking to use the system through a computerized screen, in real time, which results in improved performance in the use of this tool 31 .…”
Section: Presence Of the Checklist In The Medical Records And Data Co...mentioning
confidence: 99%